1983
DOI: 10.1152/jappl.1983.55.2.569
|View full text |Cite
|
Sign up to set email alerts
|

Regional left ventricular performance during normal and obstructed spontaneous respiration

Abstract: To clarify the effects of respiration on left ventricular (LV) dimensions and shortening, we studied chronically instrumented dogs with endocardial sonomicrometer crystals in the anterior-posterior (AP), septal to lateral (SL), and long axes (LA) following pericardiectomy. Ten anesthetized dogs were examined during spontaneous unobstructed respiration, partial inspiratory obstruction (PIO), and Mueller maneuvers (MM). During unobstructed inspiration, end-diastolic dimensions (EDD) demonstrated a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This inspiratory-induced pooling of blood expands the pulmonary vasculature, which acts as a capacitance reservoir, and results in reduced LV filling [7,16]. Finally, a last possibility is that the inspiratory increase in RV volume may cause a leftward displacement of the interventricular septum, which leads to decreased LV compliance and could limit LV filling [8,10,14,3032]. The physical constraint of the pericardium appears to contribute to this interaction as it was demonstrated that ventricular interdependence is reduced following pericardectomy in dogs [19].…”
Section: Within-breath Variation In Stroke Volume During Resting Sponmentioning
confidence: 99%
See 1 more Smart Citation
“…This inspiratory-induced pooling of blood expands the pulmonary vasculature, which acts as a capacitance reservoir, and results in reduced LV filling [7,16]. Finally, a last possibility is that the inspiratory increase in RV volume may cause a leftward displacement of the interventricular septum, which leads to decreased LV compliance and could limit LV filling [8,10,14,3032]. The physical constraint of the pericardium appears to contribute to this interaction as it was demonstrated that ventricular interdependence is reduced following pericardectomy in dogs [19].…”
Section: Within-breath Variation In Stroke Volume During Resting Sponmentioning
confidence: 99%
“…Moreover, pulmonary function in patients with heart failure is improved after cardiac transplant suggesting that pulmonary limitations are partly caused by the greater intrathoracic space occupied by the heart [45]. This increased heart–lung interdependence in patients with heart failure suggests that lung inflation could influence LV filling through mechanical compression of a less compliant left ventricle [30]. This possibility is also supported by findings that chest wall strapping of healthy individuals, in order to increase the competition for intrathoracic space between heart and lungs, resulted in a reduced stroke volume [15].…”
Section: Heart–lung Interdependencementioning
confidence: 99%
“…Twelve healthy, adult mongrel dogs (20-35 kg) were instrumented under halothane anesthesia, through a left lateral thoracotomy, using sterile technique (Robotham et al, 1983). The instrumentation ( Fig.…”
Section: Instrumentationmentioning
confidence: 99%
“…During spontaneous inspiration, a decrease in the left ventricular septal-lateral dimension consistent with compression of the heart in the lateral direction has been reported [18]. However, SCHARF et al [19] showed that the compressive effect of lung inflation probably plays a less important role during spontaneous inspiration than during mechanical ventilation with positive end-expiratory pressure.…”
Section: Effects On Left Ventricular Afterloadmentioning
confidence: 91%